PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE, AUDIT BRAND NAME DAN UKURAN PERUSAHAAN TERHADAP KONSERVATISME AKUNTANSI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016-2018 - Emi Febriani; Maslichah Maslichah; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2020)
This study aims to determine the Effect of Good Corporate Governance Mechanisms, Brand Name Audit and Company Size on Accounting Conservatism in Manufacturing Companies Listed on the Indonesia Stock Exchange in 2016-2018. Based on the number of calculations obtained 49 companies selected to be sampled. The results of the analysis using multiple linear regression analysis show Managerial Ownership, the Proportion of Independent Commissioners, Institutional Ownership, Brand Name Audit and Company Size simultaneously have a significant effect on Accounting Conservatism. Partial test results show Managerial Ownership, Proportion of Independent Commissioners and Institutional Ownership does not have a significant effect on Accounting Conservatism. Partial test results show that Brand Name Audit and Company Size have a significant effect on Accounting Conservatism.Keywords : Good Corporate Governance Mechanism, Brand Name Audit,  Company Size, Accounting Conservatism.